Terebra limatula Dall,1889 and T. acrior Dall, 1889 (Gastropoda: Terebridae); two problematic taxa from the western Atlantic - Garcia, Emilio F. (Zootaxa, 2012)
In a recent paper Terryn (2011) synonymized Terebra limatula Dall, 1889 and T. l. var. acrior Dall, 1889. This paper proposes that the two taxa are separate species; and that Terryn’s determination that Terebra crassireticula Simone, 1999 is a junior synonym of T. limatula may also be in error.